Numerical Spline Method for Simulation of Stochastic Differential Equations systems - Mahmoud, Suliman; Al-Wassouf, Ahmad; Ehsaan, Ali (Journal of natural sciences, life and applied sciences, 2021)
In this paper, numerical spline method is presented with collocation two parameters for solving systems of multi-dimensional stochastic differential equations (SDEs). Multi-Wiener’s time-continuous process is simulated as a discrete process, and then the mean-square stability of proposed method when applied to a system of two-dimensional linear SDEs is studied. The study shows that the method is mean-square stability and third-order convergent when applied to a system of linear and nonlinear SDEs. Moreover, the effectiveness of our method was tested by solving two test linear and non-linear problems. The numerical results show that the accuracy and applicability of the proposed method are worthy of attention.